A pós-modernidade em Campos de Carvalho: um estudo sobre a liquidez, o desvario e o niilismo nos romances A lua vem da Ásia e O púcaro búlgaro - Ribeiro Júnior, Armando (2013)
Works on the novelist Walter Campos de Carvalho (1916-1998) are rare. Great obscurity falls on that works in the attempt of definition. Although, after being decades absent, he had returned to the pages of the press in the last years, thanks to the theatrical adaptations of his four novels, there are still an incomprehensible silence about his literature which is often merely taken as a humoristic experience. Thus, this dissertation has as its principal objective to observe the development of postmodernity, according to the sociologist Zygmunt Bauman s view, of the novels A Lua vem da Ásia (1956) e O Púcaro Búlgaro (1964), respectively the first and the last of Campos de Carvalho s novels, showing that the novelist in fact anticipated narrative experiences proper of contemporaneity and that part of the incomprehension about him is due to this fact.